Artificial repair material capable of being subjected to photosensitive shaping and used for ear surgery modeling operation and preparation method of artificial repair material

By developing a photosensitive plastic repair material composed of bioactive inorganic fillers, organic monomers and photoinitiators, the problem of insufficient bone defect repair materials in ear surgery has been solved, and the material has been rapidly cured and has good mechanical properties. performance and biocompatibility, promoting effective repair of bone defects and simplification of surgery.

CN119345459APending Publication Date: 2025-01-24INST OF CHEM CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475644.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

Smart Images

  • Figure CN119345459A_ABST
    Figure CN119345459A_ABST
Patent Text Reader

Abstract

The invention discloses an artificial repair material capable of photosensitive shaping and used for an ear surgery modeling operation and a preparation method of the artificial repair material, and belongs to the field of biomedical materials. The artificial repair material for the ear surgery modeling operation consists of three parts, namely a bioactive inorganic filler, an organic monomer and a photoinitiator, wherein the mass percentage content of the bioactive inorganic filler is 30%-70%. The artificial repair material disclosed by the invention can be subjected to photosensitive shaping, and has excellent biocompatibility, stable mechanical properties and good biological activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, and in particular to an artificial repair material capable of photosensitive shaping for ear surgery modeling and a preparation method thereof. Background Art

[0002] In the 1960s, after the introduction of microscopes into ear surgery, ear surgery entered the era of ear microsurgery. Compared with the naked eye era, it can achieve more delicate operations and clearer lesion removal. However, this requires a relatively wide range of surgical exposure and large-scale bone removal, making open middle ear surgery popular. In order to cater to the realization of the minimally invasive concept, a variety of different clinical classifications of middle ear cholesteatoma and a large number of improvements and evolutions in middle ear surgery have emerged, all in order to find a balance between completely removing lesions and retaining structural functions. With the continuous maturity and progress of ear endoscope technology in the past two decades and its extensive promotion and application, ear endoscopes have achieved the dual goals of minimally invasive and lesion removal better than microscopes to a certain extent. Nevertheless, whether it is the microscope method or the ear endoscope surgery method, the problem that neither of them solves is that there are many clinical classifications for the same case, the clinical schemes are diverse, and there is no relatively unified treatment consensus and guidelines. This leads to a long learning curve for grassroots doctors to learn and master ear surgery techniques, a lack of standardized evaluation criteria in clinical practice, and the failure to promote and apply ear surgery techniques.

[0003] It is conceivable that the various types and technical improvements of microscopes and otoscopes are all aimed at completely removing the lesions while preserving the bony structure of the external auditory canal as much as possible. The crux of all this is that there is no good bone ear canal repair material. If there is an ideal repair material, after the surgical field is sufficiently exposed, the lesions are completely removed, and then the ear canal bone wall is simply and efficiently repaired with this material, all surgical methods can be simplified into a standardized surgical method, which will completely change the current status of ear surgery.

[0004] Based on the above considerations, it is necessary to develop an artificial repair material that meets the following characteristics: (1) The original state of the material is a solid or semi-solid state that is easy to shape, and can be shaped as needed and applied to the bone defect area of ​​the surgical cavity. (2) Under specific stimulation, it can be solidified to greatly improve the mechanical strength and achieve space-occupying repair of the bone defect. (3) At the same time, the material should have mechanical stability, and the body fluid tissue in the surgical cavity, such as blood, cerebrospinal fluid, and irrigated saline, should have no effect on the mechanical properties of the biomaterial. (4) In addition, after the biomaterial repairs the bone defect, epithelial tissue still needs to grow along its surface and cover the entire bone defect, so it must also have a certain degree of biocompatibility. (5) Finally, after the material repairs the bone defect, it can meet the long-term imaging follow-up after surgery and can be imaged under CT for imaging evaluation. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an artificial repair material capable of photosensitive shaping for modeling ear surgery and a preparation method thereof. The artificial repair material of the present invention is photosensitively reshaping, has excellent biocompatibility, stable mechanical properties and good biological activity.

[0006] The present invention firstly provides an artificial repair material for modeled ear surgery, which consists of three parts: a bioactive inorganic filler, an organic monomer and a photosensitive initiator; wherein the mass percentage of the bioactive inorganic filler is 30% to 70%.

[0007] In the above-mentioned artificial repair material, the mass percentage of the bioactive inorganic filler is 50%, 55%, 60% or 65%.

[0008] In the above artificial repair material, the bioactive inorganic filler is at least one of bioactive glass, tricalcium phosphate and hydroxyapatite.

[0009] In the above-mentioned artificial repair material, the particle size of the bioactive inorganic filler is less than 400 mesh (diameter less than 38 μm), 400-200 mesh (diameter 38-74 μm), 200-120 mesh (diameter 74-125 μm) or 120-80 mesh (diameter 125-177 μm).

[0010] In the above-mentioned artificial repair material, the bioactive glass is at least one of 45S5, 58S, pH neutral bioactive glass (PSC), A / W glass-ceramics and micro-nano bioactive glass.

[0011] In the above artificial repair material, the organic monomer is at least one of bisphenol A dimethacrylate glycidyl ester (bis-GMA), glycerophosphoric acid dimethacrylate (GPDM), urethane dimethacrylate (UDMA), triethylene glycol dimethacrylate (TEGDMA), methyl methacrylate (MMA), 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, bisethoxy bisphenol-A dimethacrylate, hydroxyethyl methacrylate, styrene, decanediol dimethacrylate and dimethylaminoethyl methacrylate (DMAEMA); The photoinitiator is at least one of camphorquinone (CQ), dimethyl benzoate (DMPA), diphenylmethane, hydroxycyclohexyl acetophenone and dihexyloxyacetophenone.

[0012] In the above artificial repair material, based on the total mass of the organic monomer and the photoinitiator, the mass percentage of the photoinitiator is 0.1% to 1%; the balance is the organic monomer.

[0013] Specifically, the mass percentage of the photoinitiator is 0.2%.

[0014] In the above artificial repair material, the organic monomers are bisphenol A glycidyl dimethacrylate, triethylene glycol dimethacrylate and dimethylaminoethyl methacrylate; The photoinitiator is camphorquinone; Based on the total mass of bis-GMA, TEGDMA, DMAEMA and CQ, the mass percentage of bis-GMA is 20-70%, the mass percentage of DMAEMA is 0.1%-1%, the mass percentage of CQ is 0.1%-1%, and the balance is TEGDMA; In one embodiment of the present invention, based on the total mass of bis-GMA, TEGDMA, DMAEMA and CQ, the mass percentage of bis-GMA is 49.5%, the mass percentage of TEGDMA is 49.5%, the mass percentage of DMAEMA is 0.8%, and the mass percentage of CQ is 0.2%.

[0015] Furthermore, the present invention provides a method for preparing the above artificial repair material, comprising the following steps: uniformly mixing the bioactive inorganic filler, organic monomer and photosensitive initiator.

[0016] The preparation method specifically comprises the following steps: mixing the organic monomer and the photosensitive initiator, stirring to obtain a clear and transparent mixed solution, and then mixing the mixed solution with the bioactive inorganic filler.

[0017] In the above-mentioned preparation method, the preparation method also includes the step of curing the mixture under blue light with a wavelength of 400-500nm.

[0018] Specifically, the irradiation curing time is 10-20 seconds, and specifically may be 10 seconds.

[0019] Finally, the present invention provides the use of the above artificial repair material in preparing patterned repair materials for ear surgery; or Application of the above-mentioned artificial repair materials in modeled ear surgery.

[0020] The present invention has the following advantages: (1) The artificial repair material of the present invention has excellent plasticity. By changing the content of inorganic bioactive fillers, its bulk viscosity can be changed within a wide range, thereby facilitating shaping during surgery; before irradiation with light, it can be filled to adapt to defect areas of different shapes; (2) The artificial repair material of the present invention can be cured within 10 seconds under the irradiation of blue light with a wavelength of 400-500 nm; (3) The artificial repair material of the present invention has excellent and stable mechanical properties and can maintain its mechanical properties for a long time without being affected by the body fluid environment; (4) Due to the introduction of inorganic bioactive fillers, the artificial repair material can exhibit excellent biocompatibility and bioactivity in physiological environments (such as saliva and body fluids), and can better induce cell proliferation and adhesion on its surface, realize the growth of epithelial tissue along its surface, and ultimately cover the entire bone defect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are digital photos of the injection and extrusion of artificial repair materials in Examples 1-4.

[0022] Figure 2 It is the bending strength of the artificial repair material in Examples 1-4 after curing for 24 hours.

[0023] Figure 3 It is the flexural strength of the artificial repair materials shaped in Examples 1-4 after being immersed in simulated body fluid for seven days.

[0024] Figure 4 XRD test results of the artificial repair materials shaped in Examples 1-4 after curing for 24 hours Figure 5 These are the XRD test results of the artificial repair materials shaped in Examples 1-4 immersed in simulated body fluid for seven days.

[0025] Figure 6 This is a SEM photograph of the artificial repair material shaped in Example 4 immersed in simulated body fluid for seven days.

[0026] Figure 7 This is a photograph of the processed sample of the artificial repair material shaped in Example 4 after being embedded in a nude mouse for one month. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.

[0028] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0029] The quantitative tests in the following examples were all repeated three times, and the results were averaged.

[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0031] Example 1 (1) 4.95 g of bis-GMA (bisphenol A diglycidyl methacrylate, CAS No.: 1565-94-2), 4.95 g of TEGDMA (triethylene glycol dimethacrylate, CAS No.: 109-16-0), 0.08 g of DMAEMA (dimethylaminoethyl methacrylate, CAS No.: 105-16-8) and 0.02 g of CQ (camphorquinone, CAS No.: 10373-78-1) were mixed and stirred at 60 °C for 1 h in the dark to obtain a clear and transparent mixed solution of organic monomers and photoinitiators for later use.

[0032] (2) Add 0.5 g of PSC bioactive glass with a particle size of less than 38 μm to 0.5 g of the above mixed solution, place the mixture in a degassing stirrer and mix for 2 minutes to obtain an artificial repair material.

[0033] (3) The artificial repair material is moved into a designated mold and irradiated with blue light having a wavelength of 400 to 500 nm for 10 seconds for curing. After demolding, the fixed artificial repair material is obtained.

[0034] The performance of the samples was tested using the following method: a. First, the artificial repair material obtained in step (2) is placed in a syringe to detect whether it has fluidity before solidification.

[0035] b. At room temperature, the flexural strength of the artificial repair material obtained in step (3) was tested using an MTS E42 universal tensile testing machine. The strength was tested after curing for 24 hours and after being immersed in simulated body fluid (SBF) for one week. During the flexural strength test, the sample was prepared into a 2mm×2mm×25mm rectangle, and the test rate was 0.5mm / min.

[0036] c. Soak the sample in SBF for one week and use an X-ray diffractometer to test whether the sample has biological activity, with a scanning range of 5° to 70° and a scanning rate of 4° / min. Before SEM testing, adhere the sample to the SEM sample stage with conductive glue, spray gold (current 20mA, time 120s), and then use SEM to observe the cross-section and surface morphology of the sample (power-on voltage 5kV).

[0037] d. By embedding the sample into the body of a nude mouse, the sample is taken out one month later and the growth of tissue on the sample is observed.

[0038] The results showed that the artificial repair material could be squeezed out of the syringe before solidification ( Figure 1 ), indicating that it has good processability. The flexural strength of the artificial repair material before and after immersion was 85.4±9.1MPa and 87.2±6.1Mpa ( Figure 2 and Figure 3). The XRD results are significantly different from those before immersion in SBF ( Figure 4 and Figure 5 ), the diffraction peak at 31.7° is significantly enhanced, indicating that the artificial repair material has good biological activity. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is produced on the surface of the sample after immersion in SBF. The results of animal experiments prove that the in vivo tissue can effectively combine with the surface of the artificial repair material.

[0039] Example 2 (1) 4.95 g bis-GMA, 4.95 g TEGDMA, 0.08 g DMAEMA and 0.02 g CQ were mixed and stirred at 60 °C for 1 h in the dark to obtain a clear and transparent mixed solution of organic monomer and photoinitiator for later use.

[0040] (2) Add 0.55 g of PSC bioactive glass with a particle size of less than 38 μm to 0.45 g of the above mixed solution, place the mixture in a degassing stirrer and mix for 2 minutes to obtain an artificial repair material.

[0041] (3) The artificial repair material is moved into a designated mold and irradiated with visible light having a wavelength of 400 to 500 nm for 10 seconds for curing. After demolding, a fixed artificial repair material is obtained.

[0042] The performance test method is the same as that of Example 1. The results show that the artificial repair material can be squeezed out of the syringe before solidification ( Figure 1 ), indicating that it has good processability. The flexural strength of the artificial repair material before and after immersion was 105.6±12.1MPa and 108.6±17.1MPa respectively ( Figure 2 and Figure 3 ), proving that the material has good mechanical stability in body fluid environment. The XRD results are significantly different from those before immersion in SBF ( Figure 4 and Figure 5 ), the diffraction peak at 31.7° is significantly enhanced, indicating that the artificial repair material has good biological activity. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is produced on the surface of the sample after immersion in SBF. The results of animal experiments prove that the in vivo tissue can effectively combine with the surface of the artificial repair material.

[0043] Example 3 (1) 4.95 g bis-GMA, 4.95 g TEGDMA, 0.08 g DMAEMA and 0.02 g CQ were mixed and stirred at 60 °C for 1 h in the dark to obtain a clear and transparent mixed solution of organic monomer and photoinitiator for later use.

[0044] (2) Add 0.6 g of PSC bioactive glass with a particle size of less than 38 μm to 0.4 g of the above mixed solution, place the mixture in a degassing stirrer and mix for 2 minutes to obtain an artificial repair material.

[0045] (3) The artificial repair material is moved into a designated mold and irradiated with visible light having a wavelength of 400 to 500 nm for 10 seconds for curing. After demolding, a fixed artificial repair material is obtained.

[0046] The performance test method is the same as that of Example 1. The results show that the artificial repair material can be squeezed out of the syringe before solidification ( Figure 1 ), indicating that it has good processability. The flexural strength of the artificial repair material before and after immersion was 101.6±10.5MPa and 103.6±9.1MPa ( Figure 2 and Figure 3 ), proving that the material has good mechanical stability in body fluid environment. The XRD results are significantly different from those before immersion in SBF ( Figure 4 and Figure 5 ), the diffraction peak at 31.7° is significantly enhanced, indicating that the artificial repair material has good biological activity. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is produced on the surface of the sample after immersion in SBF. The results of animal experiments prove that the in vivo tissue can effectively combine with the surface of the artificial repair material.

[0047] Example 4 (1) 4.95 g bis-GMA, 4.95 g TEGDMA, 0.08 g DMAEMA and 0.02 g CQ were mixed and stirred at 60 °C for 1 h in the dark to obtain a clear and transparent mixed solution of organic monomer and photoinitiator for later use.

[0048] (2) Add 0.65 g of PSC bioactive glass with a particle size of less than 38 μm to 0.35 g of the above mixed solution, place the mixture in a degassing stirrer and mix for 2 minutes to obtain an artificial repair material.

[0049] (3) The artificial repair material is moved into a designated mold and irradiated with visible light having a wavelength of 400 to 500 nm for 10 seconds for curing. After demolding, a fixed artificial repair material is obtained.

[0050] The performance test method is the same as that of Example 1. The results show that the artificial repair material can be squeezed out of the syringe before solidification ( Figure 1 ), indicating that it has good processability. The flexural strength of the artificial repair material before and after immersion was 127.6±8.1MPa and 123.5±4.1MPa ( Figure 2 and Figure 3), proving that the material has good mechanical stability in body fluid environment. The XRD results are significantly different from those before immersion in SBF ( Figure 4 and Figure 5 ), the diffraction peak at 31.7° is significantly enhanced, indicating that the artificial repair material has good biological activity. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is formed on the surface of the sample after immersion in SBF ( Figure 6 Animal experiment results show that the in vivo tissue can effectively combine with the surface of the artificial repair material ( Figure 7 ).

Claims

1. An artificial repair material for modeled ear surgery, which consists of three parts: a bioactive inorganic filler, an organic monomer and a photosensitive initiator; wherein: The mass percentage of the bioactive inorganic filler is 30% to 70%.

2. The artificial repair material according to claim 1, characterized in that: The bioactive inorganic filler is at least one of bioactive glass, tricalcium phosphate and hydroxyapatite; The particle size of the bioactive inorganic filler is below 400 mesh, 400-200 mesh, 200-120 mesh or 120-80 mesh.

3. The artificial repair material according to claim 2, characterized in that: The bioactive glass is at least one of 45S5, 58S, pH neutral bioactive glass (PSC), A / W glass-ceramics and micro-nano bioactive glass.

4. The artificial repair material according to any one of claims 1 to 3, characterized in that: The organic monomer is at least one of bisphenol A dimethacrylate glycidyl, glycerophosphoric acid dimethacrylate, carbamate dimethacrylate, triethylene glycol dimethacrylate, methyl methacrylate, 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, bisethoxy bisphenol-A dimethacrylate, hydroxyethyl methacrylate, styrene, decanediol dimethacrylate and dimethylaminoethyl methacrylate; The photoinitiator is at least one of camphorquinone, benzoin dimethyl ether, diphenylmethane, hydroxycyclohexyl acetophenone and dihexyloxyacetophenone.

5. The artificial repair material according to any one of claims 1 to 4, characterized in that: Based on the total mass of the organic monomer and the photoinitiator, the mass percentage of the photoinitiator is 0.1% to 1%.

6. The artificial repair material according to any one of claims 1 to 5, characterized in that: The organic monomers are bisphenol A glycidyl dimethacrylate, triethylene glycol dimethacrylate and dimethylaminoethyl methacrylate; The photoinitiator is camphorquinone; Specifically, based on the total mass of bisphenol A dimethacrylate glycidyl, triethylene glycol dimethacrylate, dimethylaminoethyl methacrylate and camphorquinone, the mass percentage of bisphenol A dimethacrylate glycidyl, the mass percentage of dimethylaminoethyl methacrylate is 20-70%, the mass percentage of dimethylaminoethyl methacrylate is 0.1%-1%, the mass percentage of camphorquinone is 0.1%-1%, and the balance is triethylene glycol dimethacrylate.

7. The method for preparing the artificial repair material according to any one of claims 1 to 6, comprising the following steps: uniformly mixing the bioactive inorganic filler, organic monomer and photosensitive initiator.

8. The preparation method according to claim 7, characterized in that: The preparation method also includes the step of curing the mixture by irradiation under blue light with a wavelength of 400-500nm.

9. The preparation method according to claim 8, characterized in that: The irradiation curing time is 10 to 20 seconds.

10. Use of the artificial repair material according to any one of claims 1 to 6 in preparing a patterned repair material for ear surgery; or Use of the artificial repair material according to any one of claims 1 to 6 in modeled ear surgery.